On Academic Rankings, Unacceptable Methods, and the Social Obligations of Business Schools. (25th April 2017) - Bachrach, Daniel G.; Bendoly, Elliot; Beu Ammeter, Danielle; Blackburn, Richard; Brown, Kenneth G.; Burke, Gerry; Callahan, Ty; Chen, Kay Yut; Day, Vikki Haag; Ellstrand, Alan E.; Erekson, O. Homer; Gomez, Jaime Alonso; et al.
ABSTRACT: Inspired by recent discussions of the systematic costs that external rankings impose on academic institutions, and the undeniable shifts in the landscape of institutional data, a concerted and pragmatic re‐evaluation of ranking efforts has begun. In this study, multiple administrators and researchers representing both public and private institutions across the United States weigh in on these issues. While reaffirming the social contract we hold with society, we argue that the fundamental methodological shortcomings of existing rankings, and ultimately any ordinal ranking system, limit the value of current rankings. These shortcomings emerge from the conceptualization and the architecture of comparisons, and are evident in survey designs, data collection methods, and data aggregation procedures. Our discussion continues by outlining the minimal requirements that a socially responsible, transparent, flexible, and highly representative rating (vs. ranking) approach should employ. Ultimately, we call on academic institutions and organizing bodies to take a collective stand against existing rankings and to embrace the strategic use of multidimensional alternatives that faithfully serve prospective students, parents, and other key stakeholders. We conclude with a number of suggestions and opportunities for practice‐oriented research in the decision sciences aimed to support this fundamental shift in evaluative framing.